Assessing English Proficiency of Management and Accounting Students Using Linguaskill Business Tests Aligned with CEFR Standards - Kaloeti, Ade Kristianus (CV. Doki Course and Training, 2024)
This study aims to analyze the English language proficiency of students in Management and Accounting programs using the Linguaskill Business test and the CEFR standards. The research sample consists of 10 undergraduate students from the Management program and 10 students from the Diploma program in Management. Data, represented by test scores, were collected through the Linguaskill Business assessment. Subsequently, the data were statistically analyzed to determine the minimum, maximum, mean scores, and frequency distribution. This data was then converted into a CEFR standard table for further analysis of English language proficiency according to CEFR criteria. The findings indicate that the majority of Management and Accounting students possess basic English language skills, primarily at or below the A1 level. Some students demonstrated relatively good proficiency at the A1, A2, and a maximum of B1 levels. Therefore, it is essential to enhance the English language skills of these students, as they have not yet reached the higher levels of B2 and C1.